Participating in Research: Attitudes within the African American Church - Odulana, Adebowale (Journal of religion and health, 2014)
We assessed associations between pastor and congregant characteristics and congregant attitudes about research participation among African American churches. Respondents shared their attitudes regarding how willing, ready, and confident they were about research participation. The outcome measure, the index of research preparedness, summed responses across the domains of willingness, readiness, and confidence. Pastor age and pastor educational attainment were independently associated with a congregants' higher index of research preparedness. Young and educated pastors were significantly associated with congregant attitudes about participation preparedness, a finding that highlights the importance of the pastor regarding congregant research participation decisions.